CSR and sustainability of Islamic banking: the bankers view - Shifa Mohd Nor; Noor Azuan Hashim (Penerbit Universiti Kebangsaan Malaysia, 2015)
Islamic banking (IB) practices have spread throughout the World, not only in Muslim countries but also in the West. To sustain in the very competitive market, Islamic banking must be outstanding and resilience from other conventional banks. Hence sustainable banking theme is deemed to be relevant to its operation by incorporating corporate social responsibility (CSR) and sustainable development concepts. Little that we know about CSR and sustainable development practices of Islamic banking from the managerial views. This paper attempts to explore the social responsibility and sustainability dimension of Islamic banking in Malaysia from the management insights. This is an inductive research employing semi-structured interview survey of 11 important Islamic bankers holding various positions. Thematic analysis approach was used to analyse data. The study reveals that Islamic banks are encouraged to perform various CSR activities however activities leading to significant socioeconomic impact are still lacking. Social banking may provide the answer.